Understanding Children's and Young Adolescents' Media Practices: Reflections on Methodology - Ulrika Sjöberg (Universitetsforlaget, 2010)
The article 'Understanding children's and young adolescents' media practices: reflections on methodology' is intended to contribute to current discussions on the perception and construction of child/childhood and the surrounding digital media landscape. In the article, the researcher describes and reflects upon her own experiences with various methods (interviews, diaries, drawings and photos) used when examining children's and young adolescents' (in the age range 8-16 years) media practices, focusing on the Internet and computer games. Throughout the text, the claim of having young people's perspectives as the main point of departure in research is looked at with a critical eye. This key issue is elaborated upon, through examples from research, by discussing three main interrelated aspects - the conditions for young people to have a say in research, ethical aspects and the type of data acquired when the researcher claims to have a children's or youth perspective.